“Here I Am, I Have Come; In the Scroll of the Book, it is Written of Me” (Ps 40:8). The Private and Public Piety Advocated by Psalm 40 and the Challenges Faced by the Editors of the Psalter - Botha, Phil J (Journal for Semitics, 2025)
This article argues that Ps 40 should not be interpreted within a cultic milieu but as part of the literary context of the Psalter. As part of the conclusion of the final cluster in Book I, and thus as part of the conclusion of the first book of Davidic psalms, it is closely related to (especially) Pss 1–2 and Ps 35. When read as part of this context, it becomes clear that the psalmist, as the “servant” of YHWH, represents the in-group of faithful believers in the late post-exilic period who earnestly studied the Torah and attempted to follow its directives. They were waiting for YHWH’s intervention to save them from renegade fellow Jews and foreign overlords who oppressed them.